DOI: 10.17077/etd.hic4swj0
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure and performance of a flexible plunging airfoil

Abstract: An investigation was performed with the intent of characterizing the effect of flexibility on the flow structure and aerodynamic performance of a plunging airfoil, over a parameter space applicable to birds and flapping MAVs. Both the material properties of the airfoil and the kinematics of its motion were characterized optically. The vortex dynamics associated with the plunging motion were mapped out using particle image velocimetry (PIV), and categorized according to the behavior of the leading edge vortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This hypothesis was briefly tested by Akkala et. al [1] for a purely plunging wing however no conclusions were drawn. For future work, perturbing the flow with forced methods can help support or weaken the argument that secondary vorticity is the mechanism controls LEV attachment.…”
Section: Future Workmentioning
confidence: 97%
“…This hypothesis was briefly tested by Akkala et. al [1] for a purely plunging wing however no conclusions were drawn. For future work, perturbing the flow with forced methods can help support or weaken the argument that secondary vorticity is the mechanism controls LEV attachment.…”
Section: Future Workmentioning
confidence: 97%
“…(c) Dye visualization of the leading and trailing edge vortex structures formed by a plunging, flexible wing. Unpublished picture from previous work by the author [3]. through cross-cancellation [118,117].…”
Section: Literature Review: the Leading-edge Vortexmentioning
confidence: 99%
“…The small size of the SLV generally causes it to be neglected, yet Akkala [3] showed that its presence within the flow can help to prevent the OSV from circumnavigating the leading edge. The results obtained in this experiment also illustrate this phenomenon.…”
Section: Vorticity Flux Analysismentioning
confidence: 99%